An experimental study on monitoring of marine sediment transport by using a 3D sediment trap - Guo, Lei; Fei, Zihang; Liu, Tao; Xu, Zhihao; Yang, Xiuqing; Liu, Xiaolei (Frontiers in Marine Science, 2023)
The observation and analysis of sediment transport in oceans is an important means for the protection of the marine environment, resource development, construction engineering, and element cycling. However, traditional methods of observing sediment transport are either limited by the range of the instruments used or their own observational attributes, such that they cannot be used to accurately detect and analyze the process of transport of marine sediment. Recently, a 3D sediment trap has been proposed to compensate for the shortcomings of the various monitoring tools, but no mature method for the analytical inversion of the data obtained from this device has been developed to date. In this paper, we used the cut-off inversion of the time series of the sediment samples to establish the relationship between the particle size and concentration of the captured samples. We performed restoration tests on the process of sediment transport to establish a set of methods of flux analysis based on the velocity and turbidity of flow. An exploratory test of the efficiency of capture was used to clarify the law of influence of changes in the particle size on the efficiency of their capture. Eventually we develop an analytical method for the inversion of the sediment transport by using the corrected efficiency of capture, sample inversion and transport flux analysis.